Problems of television design in the domestic media space - Smail Д.Б.; Kuldzhashbaeva Ж.К. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2020)
. This article discusses in detail the design issues of domestic television. In the media space of Kazakhstan, the number of users of Internet resources is growing, but television still occupies the first place in the minds of people. Even video content on the Internet complements television programs. The article includes television design, its origin story and impact on society. Also, the complexities and features of television designs, harmony to increase the television audience, a logo pleasing to the eye of viewers, a splash screen, cut-off and music that touches the strings of the soul of people are considered. The advantages of the motion design structure, created by special programs for modern designers, were not left unnoticed. The requirements and tasks for the work of a TV designer are also taken into account. In addition, it describes the importance of design of television programs that influence the tastes of consumers, from children to adults. The role of color and rhythm, hue and movement for human psychology is studied in detail, the artistic level is presented to attract rating and investment.